Alternative routes of levothyroxine administration for hypothyroidism. Issue 5 (October 2020) - Ritter, Megan J.; Gupta, Suruchi; Hennessey, James V.
Abstract : Purpose of review: The aim of the article is to present the basics of oral levothyroxine (LT4) absorption, reasons why patients may have persistently elevated serum thyroid stimulation hormone (TSH) levels, and alternative strategies for LT4 dosing. Recent findings: Although oral LT4 tablets are most commonly used for thyroid hormone replacement in patients with hypothyroidism, case studies report that liquid oral LT4, intravenous, intramuscular, and rectal administration of LT4 can successfully treat refractory hypothyroidism. Summary: Hypothyroidism is one of the most common endocrine disorders encountered by primary care physicians and endocrinologists. LT4 is one of the most widely prescribed medications in the world and it is the standard of care treatment for hypothyroidism. Generally, hypothyroid patients will be treated with LT4 tablets to be taken orally, and monitoring will occur with routine serum thyroid tests, including TSH concentrations. However, many patients fail to maintain serum TSH levels in the target range while managed on oral LT4 tablets. A subset of these patients would be considered to have poorly controlled hypothyroidism, sometimes termed refractory hypothyroidism. For these patients, optimization of ingestion routines and alternative formulations and routes of administration of LT4 can be considered, including oral liquid, intravenous, intramuscular, and even rectal formulations.